Family‐centred music therapy to promote social engagement in young children with severe autism spectrum disorder: a randomized controlled study. Issue 6 (22nd November 2013) - Thompson, G. A.; McFerran, K. S.; Gold, C.
Abstract Background Limited capacity for social engagement is a core feature of autism spectrum disorder (ASD), often evident early in the child's development. While these skills are difficult to train, there is some evidence that active involvement in music‐making provides unique opportunities for social interaction between participants. Family‐centred music therapy (FCMT) endeavours to support social engagement between child and parent within active music‐making, yet the extent of benefits provided is unknown. Aim This study investigated the impacts of FCMT on social engagement abilities. Methods Twenty‐three children (36–60 months) with severe ASD received either 16 weeks of FCMT in addition to their early intervention programmes (n = 12), or their early intervention programme only (n = 11). Change in social engagement was measured with standardized parent‐report assessments, parent interviews and clinician observation. Results Intention‐to‐treat analysis for the Vineland Social Emotional Early Childhood Scale indicated a significant effect in favour of FCMT. Thematic qualitative analysis of the parent interviews showed that the parent–child relationship grew stronger. Conclusion FCMT improves social interactions in the home and community and the parent–child relationship, but not language skills or general social responsiveness. This study provides preliminary support for the use of FCMT to promote social engagement in children with severe ASD.